2012
DOI: 10.1089/jmf.2012.2282
|View full text |Cite
|
Sign up to set email alerts
|

Prickly Pear Cactus (Opuntia ficus indicavar.saboten) Protects Against Stress-Induced Acute Gastric Lesions in Rats

Abstract: The protective activity of prickly pear cactus (Opuntia ficus indica var. saboten) fruit juice and its main constituent, betanin, were evaluated against stress-induced acute gastric lesions in rats. After 6 h of water immersion restraint stress (WIRS), gastric mucosal lesions with bleeding were induced in Sprague-Dawley rats. Pretreatment of a lyophilized powder containing O. ficus indica var. saboten fruit juice and maltodextrin (OFSM) and betanin significantly reduced stress lesions (800-1600 mg/kg). Both OF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 21 publications
0
19
0
Order By: Relevance
“…Studies have investigated the capacity of betalains, mainly betanin, to scavenge free radicals in vitro, and this capacity is even higher than that of vitamin C [34,68]. Betanin has also been reported to inhibit cancer cell proliferation in vitro and in vivo [18], and it protects against acute lung injury and gastric lesions [30,69]. …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies have investigated the capacity of betalains, mainly betanin, to scavenge free radicals in vitro, and this capacity is even higher than that of vitamin C [34,68]. Betanin has also been reported to inhibit cancer cell proliferation in vitro and in vivo [18], and it protects against acute lung injury and gastric lesions [30,69]. …”
Section: Discussionmentioning
confidence: 99%
“…Rats were pretreated with daily oral doses of cactus extract (800 mg/kg), according to the protocol of Kim et al [30] with some modifications) or GSH (50 mg/kg, intraperitoneally) for five days before APAP treatment (500 mg/kg intraperitoneally; single dose). Samples of blood and liver tissue were collected 4 h after APAP intoxication for assessment of liver damage markers [45].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The fresh fruits are widely consumed, and parts are used as functional foods, therapeutics, and animal food (Feugang et al, 2006). Many studies (Deters et al, 2012;Feugang et al, 2010;Kim et al, 2012;Tesoriere et al, 2004;Zou et al, 2005) have shown that cactus pears can reduce oxidative stress and may prevent cancer.…”
Section: Introductionmentioning
confidence: 99%
“…The pretreatment with the extract protected from the hepatic and renal histopathological and oxidative damage, as manifested in the lowered TBARS and enhanced SOD, CAT and GSH-Px level. Kim et al (2012) evaluated the protective activity of O. ficus indica var. saboten fruit juice and its constituent betanin against stress-induced acute gastric lesions in rats.…”
Section: Antioxidant and Antinflammatory Activitymentioning
confidence: 99%